Antennas and site engineering for mobile radio networks - Delorme, Bruno (Antennas and propagation series, 2013)
The book presents essential information for engineers, managers, and technicians working for mobile phone equipment manufacturers, network integrators, and antenna installation companies. The book is packed with clear explanations and recommendations for avoiding problems and making the best antenna and site decisions.